Performance Evaluation of a CI Engine Using Binary, Ternary, and Quaternary Bio-Diesel Fuel Blends - Kumar, A.; Dutta, J.; Haloi, P.; Makunike, D. F. (Journal of Scientific Research, 2023)
The present study utilizes dual biodiesel-alcohol blends to evaluate the engine performance. Five test fuels were prepared on a volume basis with different constituting percentages, each consisting of 70 % pure diesel (D70), a binary blend of biodiesel: B1 (WCO30), a ternary blend of biodiesel: B2 (WCO15 and WCCO15) and three quaternary blends: B3 (WCO10, WCCO15, Bu5), B4 (WCO15, WCCO10, Bu5) and B5 (WCO10, WCCO10, Bu10). The biodiesel is made from used cooking oil. The effects of each blend on engine performance were examined by performing the engine test on a single-cylinder, four-stroke, water-cooled Kirloskar compression ignition (CI) engine at various engine speeds and loads. The indicated power (IP), brake power (BP), friction power (FP), fuel consumption (FC), and mechanical efficiency (%) were evaluated, and the experimental results show that the performance is best for B3 when run with 75 % of the maximum load capacity of the engine. The study thus justifies that to lower the density and viscosity of biodiesel fuel, adding alcohol can be acknowledged as a valuable application to boost the engine's brake thermal efficiency (BTE). This also lowers the emissions of oxides of nitrogen (NOx), carbon monoxide (CO), and hydrocarbons (HC).